Homeward bound: A dance film under water - Lilja, Efva (Sweden Deep sea, 2005)
Choreographer/professor Efva Lilja has directed a unique film in HD format in collaboration with theSwedishfilm production company Deep Sea Productions. For the first time in Swedish dance history a pieceentirelyperformed under water! Homeward Bound premieredon October 7 2005 at the SHOOT - Dance forScreen festival in the Museum of Modern Art in Stockholm. Since then it has been shown around Sweden, inNorway, Italy, England, Holland, Greece, Portugal, Argentina and most recenttly at The American DanceFestival in Durham, USA. In Italy it won a first prize at Il Coreografo Elettronico XIV FestivalInternazionaledi Videodanza in competition with 130 films from all over the world.